2001
DOI: 10.1101/lm.40001
|View full text |Cite
|
Sign up to set email alerts
|

Massed and Spaced Learning in Honeybees: The Role of CS, US, the Intertrial Interval, and the Test Interval

Abstract: Conditioning the proboscis extension reflex of harnessed honeybees (Apis mellifera) is used to study the effect temporal spacing between successive conditioning trials has on memory. Retention is monitored at two long-term intervals corresponding to early (1 and 2 d after conditioning) and late long-term memory (3 and 4 d). The acquisition level is varied by using different conditioned stimuli (odors, mechanical stimulation, and temperature increase at the antenna), varying strengths of the unconditioned stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
167
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(185 citation statements)
references
References 62 publications
16
167
1
1
Order By: Relevance
“…In rabbit eyeblink conditioning, infusions of anisomycin into the cerebellar interpositus nuclei depress both the acquisition and retention of the conditioned response (Bracha et al, 1998;Gomi et al, 1999). The role of protein synthesis has been suggested in the memory acquisition induced by the spaced training in the conditioning of the proboscis extension reflex of honey bees (Menzel et al, 2001) and in the contextual learning of fear conditioning in rats (Scharf et al, 2002).…”
Section: Role Of Protein Synthesis In Memory Transfermentioning
confidence: 99%
“…In rabbit eyeblink conditioning, infusions of anisomycin into the cerebellar interpositus nuclei depress both the acquisition and retention of the conditioned response (Bracha et al, 1998;Gomi et al, 1999). The role of protein synthesis has been suggested in the memory acquisition induced by the spaced training in the conditioning of the proboscis extension reflex of honey bees (Menzel et al, 2001) and in the contextual learning of fear conditioning in rats (Scharf et al, 2002).…”
Section: Role Of Protein Synthesis In Memory Transfermentioning
confidence: 99%
“…For example, Sutton et al (2001b) have recently identified a second (activity-dependent) form of memory for sensitization in Aplysia that is expressed in the same temporal domain as L-ITM described in the present paper (see also, Sutton et al 2001a); however, unlike the form of L-ITM examined in the present study, this form of sensitization does not require protein synthesis. In addition, Menzel et al (2001) have recently shown that 1-2 d memory for conditioning of the proboscis extension reflex in honeybees after spaced training is significantly diminished by protein synthesis inhibitors, whereas 1-2 d memory after massed training is not. Thus, whereas different temporal phases of memory may have distinct mechanisms, time alone is not sufficient to characterize the properties of memory existing in a given temporal domain.…”
Section: Multiphasic Organization Of Memory Processingmentioning
confidence: 99%
“…In particular, in a variety of tasks across species ranging from invertebrates to humans, training trials distributed over time (spaced training) typically lead to superior retention compared with training in which trials are presented with little or no rest interval (massed training) (Ebbinghaus 1885;Carew et al 1972;Salafia et al 1973;Lefebvre and Sabourin 1977;Fanselow and Tighe 1988;Tully et al 1994;Hermitte et al 1999;Muzzio et al 1999;Menzel et al 2001). Perhaps the most interesting feature of the superiority of spaced over massed training is that it is not a general effect for all temporal domains of memory but rather appears to become more pronounced with longer-lasting memories (e.g., Carew et al 1972;Tully et al 1994;Menzel 2001). Thus, an understanding of the behavioral, cellular, and molecular factors contributing to the massed versus spaced effect could yield considerable insight into the overall organization of multiple phases of memory.…”
mentioning
confidence: 99%
“…3. Olfactory conditioning: The number of conditioning trials, the inter-trial interval, and the test time point can be varied depending on the focus of the study 3,22 . 4.…”
mentioning
confidence: 99%